FINANCIAL LITERACY TO ISLAMIC BOARDING SCHOOLS IN INDONESIA; SYSTEMATIC LITERATURE REVIEW VOS VIEWER - Trimulato; Rodoni, Ahmad; Amelia, Erika (Islamuna: Jurnal Studi Islam, 2025)
The rapid development of Islamic finance in Indonesia has not been matched by adequate levels of financial literacy, particularly within Islamic boarding schools, which should serve as vital agents in promoting value-based financial education. As long-standing Islamic educational institutions, Islamic boarding schools have significant potential to support the enhancement of Islamic financial literacy among the Muslim community. This study aims to analyze the development of Islamic financial literacy research within Islamic boarding schools using a systematic literature review (SLR) approach. By mapping trends, central topics, and knowledge gaps, the research offers strategic directions for advancing financial education and policy formulation in Islamic boarding school settings. This research employs a systematic literature review method supported by bibliometric analysis using VOSviewer. Data were collected from scholarly articles published between 2014 and 2024 in indexed academic databases, such as Google Scholar, using the Publish or Perish (PoP) application. The data analysis includes keyword mapping, publication trend identification, author collaboration patterns, and qualitative thematic analysis. The findings reveal a significant increase in Islamic financial literacy research in Islamic boarding schools over the last three years, mainly focusing on basic practices such as saving and understanding fundamental Islamic finance principles. However, researcher collaboration remains limited, and the integration of financial literacy into Islamic boarding school curricula is still underdeveloped. The study recommends policy support for the adoption of digital Islamic finance and the strengthening of academic networks to empower Islamic boarding schools as strategic centers for Islamic financial education and community economic empowerment.